A study of the effects on transmission loss of water column features as modelled for an area off the east Australian coast - Jones, Adrian; Zinoviev, A.; Greening, M. (2013)
The improved accuracy of ocean and atmospheric models permits the description of water column features, and sea surface wind stress, at a resolution which suggests employment in underwater acoustic transmission applications. In an investigation of aspects of linking modelled ocean data with range-dependent acoustic transmission models, a PE transmission code was used with data generated by the BLUElink suite of ocean and atmospheric models for a deepwater region off the east Australian coast for a particular summer period. The typical presence of warm and cold core eddies was found to result in a highly variable acoustic environment. Variations in expected range to particular levels of Transmission Loss were found to be mainly related to changes in the depth of the mixed surface layer, but also due to changes in the sound speed gradient in the thermocline. The study also made a brief consideration of the likely impact of wind speed variation over the region, and the effects of modelled ocean currents on acoustic transmission. Copyright © (2013) by the Australian Acoustical Society.